The applicability of sustainable city paradigm to the city of Jerusalem: Criteria and indicators of efficiency - Jarrar, Ola M.; Al-Zoabi, Ahmad Y. (Building and environment, 2008)
Making the world's villages, towns and cities environmentally, economically and socially sustainable is humanity's most urgent challenge for the 21st century. This issue has been the focus of many researchers and several studies have been carried out in order to find the closest city form to the ethos of sustainability. Efficiency is one of the main key issues closely related to the sustainable city agenda. Since the concept of sustainable city is highly contextual, this study is concerned with the investigation of the applicability of sustainable city paradigm, in terms of efficiency, to the old city of Jerusalem. Investigation is limited to one major theoretical area, city form; and two minor theoretical areas, street system and land use. In order to carry out the investigation, the study used different methods (multi-method approach) consisting of content analysis and field survey, thus, incorporating the triangulation method in data analysis. The use of different methods was inspired by the very nature of the data collected, and the local context of Jerusalem. Also, the adoption of different methods compensated for the limited sources of data and provided strength for each method. The findings provide evidence that the parameter ‘efficiency’ of the sustainable city paradigm is applicable to the old city of Jerusalem with respect to the city's form and street system, but this is not the case for land use. The criteria and indicators that were not applicable identified a number of problems in the functioning of the city. The paradigm characterized is not a healing recipe or a blueprint. Rather, it is a flexible framework or a vision out of many others and, thus, disputable. This study provides an approach, out of many others, to investigate the applicability of the sustainable city paradigm on Arabic–Islamic cities in general and the old city of Jerusalem in particular. This approach provides a flexible framework for officials and planners to work through and vision each city's own version of sustainability.